The analysis and simulation of voltage distribution over string insulators using Matlab/Simulink - Izgi, Ercan; Inan, Aslan; Ay, Selim (TAYLOR & FRANCIS INC, 2008)
String insulators are generally used to insulate and carry the line conductor in the overhead power transmission lines. The number of insulator units depends on the operation voltage and other factors such as contamination, mechanical strength, lightning, and altitude. When AC voltage is applied to the string, the voltage distribution is non-uniform across a string insulator. To evaluate these voltages, string efficiency term is used. In conventional calculations of the voltage distribution over a string insulator and string efficiency, it is assumed that the insulator surface is clean, dry, and also there is no wind. In this study, the voltage distribution over an insulator string of suspension insulators and the string efficiency have been investigated with respect to the atmospheric conditions such as wind velocity, wind direction and contamination of insulator surface. All analysis and calculations have been carried out for an overhead power line between Karaman-Karasinir in Turkey having 66-kV voltage rating and 46 km long. Matlab/Simulink software is used for analysis.
Keywords: voltage distribution; string insulator; string efficiency; wind velocity; wind direction; contamination; Engineering